2021
DOI: 10.1101/2021.12.03.471151
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LINE-1 activation in the cerebellum drives ataxia

Abstract: Previous studies have revealed that dysregulation of long interspersed nuclear element 1 (LINE-1), a dominant class of transposable elements in the human genome, correlates with neurodegeneration1–3. Yet whether LINE-1 dysregulation is causal to disease pathogenesis has not been proven directly. Here, we demonstrate that expression of evolutionarily younger LINE-1 families is elevated in the cerebella of ataxia telangiectasia (AT) patients, which was correlated with extensive downregulation of epigenetic silen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…This finding is of interest in 21 highlighting the potential role of LINE/L1 dysregulation in pathogenesis, as found by a recent RNA-sequencing study that demonstrated cerebellar LINE/L1 activation in driving ataxia phenotype in mouse models. 54 Our analyses highlighted not only the potential for common pathogenic mechanisms for disease across hereditary ataxia, but also common biology. Intriguingly, we found no clear separation of genes causing childhood-and adult-onset ataxia using UMAP to visualise genes based on a recursively-selected set of features.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This finding is of interest in 21 highlighting the potential role of LINE/L1 dysregulation in pathogenesis, as found by a recent RNA-sequencing study that demonstrated cerebellar LINE/L1 activation in driving ataxia phenotype in mouse models. 54 Our analyses highlighted not only the potential for common pathogenic mechanisms for disease across hereditary ataxia, but also common biology. Intriguingly, we found no clear separation of genes causing childhood-and adult-onset ataxia using UMAP to visualise genes based on a recursively-selected set of features.…”
Section: Discussionmentioning
confidence: 87%
“…This finding is of interest in highlighting the potential role of LINE/L1 dysregulation in pathogenesis, as found by a recent RNA-sequencing study that demonstrated cerebellar LINE/L1 activation in driving ataxia phenotype in mouse models. 54…”
Section: Discussionmentioning
confidence: 99%
“…The deregulation of REs is closely linked with human diseases, in particular neurodevelopmental disorders. For instance, ERV dys-regulation in the brain is thought to cause several neurodevelopmental and neurodegenerative disorders (NDDs) such as schizophrenia and amyotrophic lateral sclerosis (Douville et al 2011), and LINE-1 activation drives ataxia (Takahashi et al, 2022). Of note, recent studies have emphasized the importance of differential splicing and isoform-level gene regulatory mechanisms in defining cell type and neural disease specificity (Gandal et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, the upstream regulators and how TRIM28 and SETDB1 are targeted to specific REs remain elusive. Of note, aberrant RE activation in somatic cells is closely linked with various diseases, including neural disorders (Douville et al 2011; Payer and Burns, 2019; Takahashi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In recent work, Takahashi et al concluded that L1 can drive neurodegeneration in AT, based on increased cerebellar L1 RNA abundance in AT patients, as well as ataxia and neurodegeneration in mice where L1 transcription was activated in the cerebellum via a dCas9-CRISPR approach (Takahashi et al, 2022). This intriguing study could shape strategies to treat or prevent AT in children and, for this reason, its findings warrant careful consideration.…”
Section: Mainmentioning
confidence: 99%